Analysis of the Influence of Employee Professionalism and Environmental Quality on Public Satisfaction at the Human Resource Development and Personnel Agency of Yogyakarta City - Fatwa Fatikha (PT Publikasiku Academic Solution, 2025)
The study aims to analyze the influence of employee professionalism and environmental quality on public satisfaction at the Civil Service and Human Resource Development Agency (BKPSDM) of Yogyakarta City. The study is based on the importance of improving public service quality through professional and citizen-oriented governance. The research employed a quantitative approach using logistic regression analysis, with secondary data obtained from the 2023–2024 Public Satisfaction Survey (SKM). The independent variables are employee professionalism and environmental quality, while the dependent variable is public satisfaction. The results show that employee professionalism has a positive and significant effect on public satisfaction with an Exp(B) value of 121.346 (sig. 0.000), while environmental quality also significantly affects public satisfaction with an Exp(B) value of 2.489 (sig. 0.024). The Nagelkerke R Square value of 0.625 indicates that both variables explain 62.5% of the variation in public satisfaction. These findings emphasize that improving employee professionalism and the service environment quality are key factors in enhancing public satisfaction with government services at BKPSDM Yogyakarta City.